2002
DOI: 10.1037/0021-9010.87.6.1020
|View full text |Cite
|
Sign up to set email alerts
|

Selection fairness information and applicant reactions: A longitudinal field study.

Abstract: Although laboratory studies have found that selection information can affect applicant perceptions, this has not been tested in the field. The authors followed 2 cohorts of police applicants (N ϭ 274) in a longitudinal study to examine the relationship between information, applicant perceptions, and behavior (e.g., turnover). Information was related to perceived fairness measured at the time of testing and 1 month later when applicants received their results. Information moderated the relationship between outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
165
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(170 citation statements)
references
References 31 publications
4
165
0
1
Order By: Relevance
“…Ryan and Ployhart (2000) cited job type as a related variable that may moderate the effects of applicant reactions. Truxillo et al (2002) cited job type as a possible interpretation for why organizational attractiveness was so high at all time points in their study. Job type could be expected to moderate applicant reactions in a few ways.…”
Section: Selection Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Ryan and Ployhart (2000) cited job type as a related variable that may moderate the effects of applicant reactions. Truxillo et al (2002) cited job type as a possible interpretation for why organizational attractiveness was so high at all time points in their study. Job type could be expected to moderate applicant reactions in a few ways.…”
Section: Selection Contextmentioning
confidence: 99%
“…For example, providing information to applicants at the beginning of a test has been found to be a simple yet meaningful way to influence candidate reactions (see Horvath et al, 2000;Truxillo et al, 2002) and has been demonstrated meta-analytically to affect a number of applicant reactions . Thus, the provision of pretest information may serve as a valuable buffer for the potentially negative effects of testing characteristics (type of test, selection context) on test reactions.…”
Section: Interventionsmentioning
confidence: 99%
“…To my knowledge, no study has attempted to trace the naturalistic effect of time in reactions after the procedure. However, this speculation is consistent with research that shows that while applicant reactions appear to have significant effects on applicant intentions when reactions are measured concurrently with the procedure, the effects are not as intense when measured after the procedure (Hausknecht et al, 2004;Truxillo et al, 2002). Hausknecht et al have suggested several possible reasons for the change in applicant reaction intensity.…”
Section: Naturalistic Changessupporting
confidence: 69%
“…This model was based on previous organizational justice research and focused on procedural justice (Leventhal, 1980;Thibaut & Walker, 1975), which concerns characteristics of the selection procedure such as job relatedness, opportunity to perform, and freedom from bias; distributive justice (Adams, 1965;Cohen, 1987), which concerns the fairness of the distribution of outcomes based on equity and social Self-Serving Bias 7 comparisons; and interactional justice (Bies & Moag, 1986), which concerns the quality of the interpersonal treatment received during the selection procedure. While studies based on the organizational justice model have enhanced our understanding of applicant reactions and have produced a wide array of insights into the effect of perceived fairness and organizational intentions and outcomes (e.g., Hausknecht et al, 2004;Truxillo et al, 2002;Paronto, 2006), Ployhart andHarold (2004) have noted that justice theory has not been as successful in explaining the mechanisms behind the formation of justice judgments. Recent organizational justice models, such as fairness heuristic theory (Lind, Kray & Thompson, 2001) and fairness theory (Folger & Cropanzano, 2001), have provided insights into the formation of justice judgments and have helped explain the relationship between justice judgments and behavioral outcomes of interest to the organization.…”
Section: Self-serving Biasmentioning
confidence: 99%
See 1 more Smart Citation